Emerging cellular technologies and the future - (:unkn) unknown (My University, 2015)
This paper includes information on various areas related to Global system for Mobile communication (GSM) which includes; GSM Systems Engineering and Network Management, GSM: Base Station Subsystem Engineering, GSM: Network Switching Subsystem Engineering, GSM: GPRS and EDGE Engineering, GSM: Satellite communication Engineering. The other issues discussed include a roadmap to M-commerce and globalization.
Paper presented at ICT confrence of 2006
This paper includes information on various areas related to Global system for Mobile communication (GSM) which includes; GSM Systems Engineering and Network Management, GSM: Base Station Subsystem Engineering, GSM: Network Switching Subsystem Engineering, GSM: GPRS and EDGE Engineering, GSM: Satellite communication Engineering. The other issues discussed include a roadmap to M-commerce and globalization.
Keywords: Mobile commerce; e-commerce; Cellular technology